2012
DOI: 10.1186/1743-422x-9-194
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic human papillomavirus genital infection in southern Iranian women: population-based study versus clinic-based data

Abstract: BackgroundEpidemiological studies on genital human papilloma viruses infection (HPVs) in general population are crucial for the implementation of health policy guidelines for developing the strategies to prevent the primary and secondary cervical cancer. In different parts of Iran, there is a lack of population-based studies to determine the prevalence of HPV in the general population. The aim of this population-based study is to compare the prevalence rate of genital HPV infection among reproductive women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Many studies have shown conflicting results about requirement vaccination against HPV infection in Iran (Eghbali et al, 2012;Haghshenas et al, 2013). On the other hand insurance companies do not cover specific cancer screening tests and this is another challengeable issue in CCPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown conflicting results about requirement vaccination against HPV infection in Iran (Eghbali et al, 2012;Haghshenas et al, 2013). On the other hand insurance companies do not cover specific cancer screening tests and this is another challengeable issue in CCPP.…”
Section: Discussionmentioning
confidence: 99%
“…Most epidemiological data for HPV infection, cervical neoplasia, abnormal cervical cytology and normal Pap smears come from local studies in different hospitals or laboratory assays of different geographical areas. But in fact for the fulfillment of health policy strategies for the prevention of cervical cancer is required to the data on cervical cancer is collected in the general population (Eghbali et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A population based study conducted in Southern Iran revealed very low genital HPV prevalence of 0.6% and clinic based study from the same locality reported prevalence of 5% among women. Among 799 women in the age group of 21-50 years participated in the Iran study cervical samples from only 5 pregnant women were tested positive (Eghbali et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…HPV‐positive and HPV‐negative (water) controls were included in each run. The amplified products were visualized by electrophoresis on 2% agarose gels containing ethidium bromide (0.5 mg/mL) …”
Section: Methodsmentioning
confidence: 99%
“…4 However, few studies have correlated HPV DNA in urine with the pathologic effect of HPV on the cervix. 4,[11][12][13][14] The aim of the present study was to evaluate the sensitivity of the urine test for high-risk HPV DNA types in the detection of high-grade squamous intra-epithelial lesions and to correlate urine test data with pathologic precancerous lesions in Egypt.…”
mentioning
confidence: 99%